GAMELAN SEBAGAI IDE PENCIPTAAN MOTIF BATIK TERAPAN DENGAN PEWARNA ALAM MANGROVE - Carsita, Carsita; Kurniawati, Dwi Wahyuni (Eduarts: Jurnal Pendidikan Seni, 2024)
This study project is entitled "Gamelan as the idea of creating applied Batik motifs with Mangrove natural dyes". The author chose batik as a means to preserve culture and develop batik design in order to strengthen the identity and excellence of Indonesia's creative industries by presenting Javanese Gamelan as an inspiration for batik motifs. According to the subject matter, the purpose of making this batik work is to produce applied batik work with Javanese Gamelan motif inspiration. In the process of creating this batik work, the author uses mangrove natural dyes as an effort to maintain health and minimize environmental pollution. Media to support the process of making batik, such as pencils, stoves, pans, canting, night or batik candles, large pots, and large tubs. The materials used are paper, primissima mori cloth, mangrove bark, quicklime, tunjung and soda ash. The process of creating works includes the visualization of ideas in the form of sketches and designs, then they are applied to the fabric. The technique used in the creation of this batik is a writing technique. The authors in this study project produced eight works. The works have titles, namely Nadindra, Pramudya, Adilawaga, Asirwada, Adicandra, Hardiyata, Ranjana, and Wagindra. The Motif presented is a form of stylization of Javanese Gamelan instruments with various approaches to the discovery of ideas in making motifs. Coloring in batik works that serve as clothing material becomes interesting because it uses natural mangrove bark dyes that are rarely used by batik craftsmen in general. The color tones produced from mangrove natural dyes are considered harmonious with the gamelan object stylization that has shades of tradition. In addition, the practical implementation of this mangrove natural dye, as an effort to make batik safe when used and blend in with nature.